1998
DOI: 10.1161/01.atv.18.10.1523
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids in Atherosclerosis and Vascular Biology

Abstract: Abstract-Sphingolipids and their metabolic products are now known to have second-messenger functions in a variety of cellular signaling pathways. Lactosylceramide (LacCer), a glycosphingolipid (GSL) present in vascular cells such as endothelial cells, smooth muscle cells, macrophages, neutrophils, platelets, and monocytes, contributes to atherosclerosis. Large amounts of LacCer accumulate in fatty streaks, intimal plaque, and calcified intimal plaque, along with oxidized low density lipoproteins (Ox-LDLs), gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(199 citation statements)
references
References 87 publications
11
185
0
3
Order By: Relevance
“…Recent studies have shown that ceramide stimulates the production of ROS in human endothelial cells [58]. Superoxide production was noted to be stimulated 4-fold when aortic smooth muscle cells were incubated with lactosylceramide (LacCer) [14]. Similarly, Yeh et al noted that the only analogue of ceramide to induce superoxide generation was LacCer, via a plasma membrane associated NADPH oxidase [59].…”
Section: Ceramide and Reactive Oxygen Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that ceramide stimulates the production of ROS in human endothelial cells [58]. Superoxide production was noted to be stimulated 4-fold when aortic smooth muscle cells were incubated with lactosylceramide (LacCer) [14]. Similarly, Yeh et al noted that the only analogue of ceramide to induce superoxide generation was LacCer, via a plasma membrane associated NADPH oxidase [59].…”
Section: Ceramide and Reactive Oxygen Speciesmentioning
confidence: 99%
“…They are not found in a free form in plasma, but rather are associated with lipoproteins and are particularly abundant in LDL [14]. Additionally, sphingolipids have not been found in lipoprotein deficient plasma, but have been associated with LDL in both normal subjects and patients with familial hypercholesterolemia [15,16].…”
Section: Lipoproteins and Ceramidementioning
confidence: 99%
“…Preincubation of cells with the antioxidant Nacetylcysteine (NAC) was found to completely abolish the shear-induced superoxide production and significantly inhibit the ICAM-1 expression. Also, D-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), attenuates the shear-induced activation of GalT-2, superoxide production and ICAM-1 expression (Yeh et al, 2001;Chatterjee, 1998). The triggering of an inflammatory reaction following activation of transcription factors NF-κB and AP-1 causes phenotypic modulation of medial vascular smooth muscle cells and their migration and subsequent proliferation in the intimal layer; increased extracellular matrix production by these vascular smooth muscle cells increases the volume of intimal tissue causing neointimal hyperplasia, ultimately leading to restenosis (Krueger et al, 2006;Mitra and Agrawal, 2006).…”
Section: Ceramide and Cardiovascular Disordersmentioning
confidence: 99%
“…We conclude that NADPH oxidase-mediated superoxide production and subsequent peroxynitrite formation mediate ceramide-induced endothelial dysfunction in small coronary arteries. lipids; vasorelaxation; endothelium; signal transduction; free radicals; nitric oxide CERAMIDE, a sphingolipid, has been reported to serve as a signaling molecule in different cell types, including vascular endothelial cells, where it is involved in the regulation of numerous cellular processes, such as ion channel activity, endothelial cell proliferation and apoptosis, and vasomotor responses (7,15,16,19,27). With respect to vasomotor regulation, previous studies from our laboratory have shown that ceramide attenuates endothelium-dependent vasorelaxation in bovine small coronary arteries, which is associated with an increase in superoxide (O 2 Ϫ ⅐) production and a subsequent decrease in nitric oxide (NO) concentrations in vascular endothelial cells (31).…”
mentioning
confidence: 99%